14th International Research Conference - FARU 2021 2021
DOI: 10.31705/faru.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plant and Equipment Operators in Building Construction Projects in Sri Lanka

Abstract: The construction industry, which is a labour intensive and skill development of the industry would yield both economic and social returns to the national economy. Among other occupational categories, there is a significant demand for the plant and equipment (P&E) operators in the construction industry. Nevertheless, limited numbers of research are available on the said area. Hence, the aim of this paper is to investigate the status of P&E operators in Sri Lankan building construction projects. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In every construction, P&E is built to perform a specific function. The selection of different types of P&E depends on the size of the work and the project's economy, making the construction process easier and faster (Waidyasekara, Ridmika, Sandagomika, & Konara, 2021). These plants come in various sizes and perform a variety of tasks.…”
Section: Plant and Equipment Operatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…In every construction, P&E is built to perform a specific function. The selection of different types of P&E depends on the size of the work and the project's economy, making the construction process easier and faster (Waidyasekara, Ridmika, Sandagomika, & Konara, 2021). These plants come in various sizes and perform a variety of tasks.…”
Section: Plant and Equipment Operatorsmentioning
confidence: 99%
“…Cranes, forklift trucks, beakers, compacters, concreting plants, earth-moving plants, and piling plants are some of the main plants and equipment utilised in the Sri Lankan construction industry (Basnayake & Premathilaka, 2015). According to the study conducted by Waidyasekara et al (2021), the P&E have been identified under major two categories of movable and immovable. Accordingly, the earth moving machine, piling machine, crane, lifting equipment, generator machine, compressor, compacting machine, and vehicles have been identified under movable P&E while the Asphalt plant, Batching plant, Crusher plant, and Sand feeding machines have been highlighted under the immovable plant and machinery operators.…”
Section: Plant and Equipment Operatorsmentioning
confidence: 99%
See 3 more Smart Citations